The Application of Bi‐Doped TiO2 for the Photocatalytic Oxidation of Formaldehyde. Issue 6 (6th March 2022) - Sun, Yiran; Feng, Bowen; Li, Qianchen; Tian, Chengcheng; Ma, Liang; Li, Zongzhe
Abstract: The photocatalytic oxidation technology has a great potential for the removal of volatile organic compounds (VOCs). In this research, a novel TiO2 /Bi2 O3 catalyst is developed to degrade indoor formaldehyde by the photocatalytic oxidation technology. The TiO2 /Bi2 O3 catalysts with different mass fractions of Bismuth(Bi) are prepared by impregnation method. The characterizations of the TiO2 /Bi2 O3 catalysts by X‐ray diffraction (XRD), ultraviolet–visible (UV–vis) spectrophotometry, and Brunauer–Emmett–Teller analyses suggest that the doping of TiO2 with Bi neither changes the crystal structure nor the crystal phase of the TiO2, but increases the number of mesopores on the TiO2 /Bi2 O3 surface and the specific surface area of the TiO2 /Bi2 O3 . By optimizing such parameters as the flow rate; the concentration; and the relative humidity of formaldehyde, the mass fraction of Bi, and the loading amount of the catalyst, a formaldehyde degradation efficiency as high as 96% is obtained. Abstract : This paper prepares Bi doped TiO2 photocatalyst, and the structural characterization experiments prove that the doping of Bi changes the energy band structure. Besides, the photocatalytic performance is studied via formaldehyde degradation experiment. In that photocatalytic reaction system, the effects of flow rate, concentration, relative humidity, mass fraction of Bi and catalyst loading on the degradation process are explored.